Pattern Recognition 31st DAGM Symposium, Jena, Germany, September 9-11, 2009, Proceedings - Denzler, Joachim; Notni, Gunther; Süße, Herbert (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
This book constitutes the refereed proceedings of the 31st Symposium of the German Association for Pattern Recognition, DAGM 2009, held in Jena, Germany, in September 2009. The 56 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on motion and tracking; pedestrian recognition and automotive applications; features; single-view and 3D reconstruction; learning and classification; pattern recognition and estimation; stereo and multi-view reconstruction; image analysis and applications; and segmentation.